KEDUDUKAN DAN KEKUATAN MENGIKAT DARI NOTA KESEPAHAMAN (MEMORANDUM OF UNDERSTANDING) DALAM PERSPEKTIF HUKUM KONTRAK DI INDONESIA - Fernando Z. Tampubolon; Ningrum Natasya Sirait; Runtung Sitepu; Mahmul Siregar (USU LAW JOURNAL, 2016)
ABSTRACT Practically, Memorandum of Understanding (MOU) is commonly used by stakeholders, with various reasons, to do business transaction or inter-institutional relationship. As an agreement which is placed in pre-contract and preliminary contract, it is usually misinterpreted as a part of a contract in Indonesia so that it usually causes problems for stakeholders when it ends in legal dispute among the stakeholders. Therefore, it is necessary to do judicial normative analysis on the real position and binding force of Memorandum of Understanding, viewed from contract law in Indonesia. In this case, descriptive analytic method inductively and logically was used in primary, secondary, and tertiary legal materials in order to obtain clear description of meaning and principles found in the Memorandum of Understanding. The result of the analysis on court’s consideration and verdicts shows that Memorandum of Understanding tends to be described as a contract according to the principles and provisions in the Civil Code so that the consideration deviates from the meaning of Memorandum of Understanding; that is, initial agreement is designed by the absence of legal consequence. In other words, Memorandum of Understanding is an agreement which comes from the stakeholders before everything is started seriously through a more and complex agreement in order to avoid damages of those who are involved in the agreement. When the contract is final and conclusive, Memorandum of Understanding can be equivalent with the principles and provisions under Article 1320 of the Indonesian Civil Code and, at the same time, Memorandum of Understanding has its substantial principles and becomes just a name. Keywords: Position, Binding Force, Memorandum of Understanding, Contract